Impacto de la gestión de los programas de bienestar social en la participación activa de los colaboradores de cementos pacasmayo s.a.a. año 2014 - Varas Leon, Liliana Judith (2015)
This research relating to the impact of the management of social welfare programs in the active participation of employees of Cementos Pacasmayo SAA 2014, is of explanatory type, the same as for characterizing active participation of employees in social welfare programs. For this he had a sample of 163 employees, with frequent participation in the programs during their time of service with the company. The results of this research show that the highest percentage of workers participating in the programs influenced by their delegates, to be chosen by themselves, place their trust and feel supported to search for their own welfare. Similarly, the participation is by type of program, usually directed and those based on family and children. Also, to a lesser extent, workers are interested in learning and assist programs, leading to the failure of these programs targets, decreasing value to the company. It is important to note the influence strategies awareness and involvement of leaders for worker participation in wellness programs, it depends on the impact of their management that develops the area of social welfare in Cementos Pacasmayo SAA.